Diagnostic and statistical manual of mental disorders : DSM-5-TR - Nussbaum, Abraham M.; American Psychiatric Association (Washington, DC : American Psychiatric Association Publishing, 2022)
'DSM-5-TR includes fully revised text and references, updated diagnostic criteria and ICD-10-CM codes since DSM-5 was published in 2013. It features a new disorder, prolonged grief disorder, as well as codes for suicidal behavior available to all clinicians of any discipline without the requirement of any other diagnosis. With contributions from over 200 subject matter experts, this updated volume boasts the most current text updates based on the scientific literature. Now in four-color and with the ability to authenticate each printed copy, DSM-5-TR provides a cohesive, updated presentation of criteria, diagnostic codes, and text. This latest volume offers a common language for clinicians involved in the diagnosis and study of mental disorders and facilitates an objective assessment of symptom presentations across a variety of clinical settings-inpatient, outpatient, partial hospital, consultation-liaison, clinical, private practice, and primary care. Important updates in DSM-5-TR include 1) fully revised text for each disorder with updated sections on associated features, prevalence, development and course, risk and prognostic factors, culture, diagnostic markers, suicide, differential diagnosis, and more; 2) addition of prolonged grief disorder (PGD) to Section II; 3) over 70 modified criteria sets with helpful clarifications since publication of DSM-5; 4) fully updated Introduction and Use of the Manual to guide usage and provide context for important terminology; 5) considerations of the impact of racism and discrimination on mental disorders integrated into the text; 6) new codes to flag and monitor suicidal behavior, available to all clinicians of any discipline and without the requirement of any other diagnosis; 7) fully updated ICD-10-CM codes implemented since 2013, including over 50 coding updates new to DSM-5-TR for substance intoxication and withdrawal and other disorders'--
Section I: DSM-5 basics. Introduction -- Use of the manual -- Cautionary statement for forensic use of DSM-5 -- Section II: Diagnostic criteria and codes. Neurodevelopmental disorders -- Schizophrenia spectrum and other psychotic disorders -- Bipolar and related disorders -- Depressive disorders -- Anxiety disorders -- Obsessive-compulsive and related disorders -- Trauma- and stressor-related disorders -- Dissociative disorders -- Somatic symptom and related disorders -- Feeding and eating disorders -- Elimination disorders -- Sleep-wake disorders -- Sexual dysfunctions -- Gender dysphoria -- Disruptive, impulse-control, and conduct disorders -- Substance-related and addictive disorders -- Neurocognitive disorders -- Personality disorders -- Paraphilic disorders -- Other mental disorders and additional codes -- Medication-induced movement disorders and other adverse effects of medication -- Other conditions that may be a focus of clinical attention -- Section III: Emerging measures and models. Assessment measures -- Culture and psychiatric diagnosis -- Alternative DSM-5 model for personality disorders -- Conditions for further study -- Appendixes.
Includes index.
Keywords: Mental Disorders -- classification; Mental Disorders -- diagnosis